SNAKE AND LADDER GAME AS AN EDUCATIONAL MEDIA OF BALANCED NUTRITION GUIDELINES ON KNOWLEDGE AND ATTITUDE AMONG NURUSSALAM ISLAMIC ELEMENTARY SCHOOL STUDENTS - Azka Salsabila Rahmat; Kartika Pibriyanti; Fathimah Fathimah (Media Gizi Pangan, 2020)
Elementary School children (7 – 12 years old) are the age group who still experiencing growth and development also adequate nutritional that suitable to support it. Children having poor eating habits lead to many nutritional need can not be fulfilled optimally. To optimalize the promotion of balanced nutrition massage to the community, community-based Communication, information, and education are needed. The role of nutrition education by using media is to help the prosess of sending nutritional messages and motivate the target person so that the nutritional message given can be well recived. Method : used quasi experimental with pre-post test control group design with respondents each group 41 students. The analysis data was tested using Wilcoxon and Mann Whitney.There was significant differences in the knowledge and attitude average of snake and ladder Media group from pretest and postest (p=0.003) and  (p=0.006). There was significant differences in the knowledge in the media lectures from pretest and postest (p=0.000) difference and there was no significant difference in the attitude (p=0.442). There was no significant difference of knowledge between snakes and ladders with a lecture (p=0.063) and there was a significant difference in the attitude (p=0.014). The snake-ledder game media with lecture method increase the knowledge and attitude. But the lecture methode only increased the knowledge. Keywords: attitude, balanced nutrition guidelines, knowledge, snakes and ladders game.